2023
DOI: 10.3390/insects14050487
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the Addition of Tenebrio molitor and Hermetia illucens on the Physicochemical and Sensory Quality of Cooked Meat Products

Barbara Lemke,
Lisa Siekmann,
Nils Th. Grabowski
et al.

Abstract: The use of proteins from insects, plants, microalgae, fungi or bacteria as an alternative to proteins of animal origin such as meat, fish, eggs or milk can meet the worldwide protein demand in the future. As the consumption of whole insects might be problematic or unacceptable for many consumers, especially in European countries, the use of homogenized insects or protein extracts from insects for the production of products might be a possibility to overcome general acceptability problems. However, the quality … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…The presence of glycosidic forms of quercetin has also been reported in Carolina locust ( Dissoteira carolina ) as resulting from the absorption of quercetin glycosides from the plant tissues [ 27 ]. Overall, our data on the phenolic composition of insect-added cooked burgers are difficult to compare with the existing literature; in this regard, the majority of the published works are based only on the evaluation of the technological properties of the formulated meat products (such as texture parameters, color, and cooking properties) [ 28 , 29 ]. For example, Cavalheiro et al [ 29 ] recently tested the potential of cricket ( A. domesticus ) flour as a lean meat replacer in the development of beef patties, demonstrating that the incorporation of up to 5.0% ( w / w ) of cricket flour into beef patties was optimal in terms of the composition, technological, sensorial, and cooking properties.…”
Section: Resultsmentioning
confidence: 99%
“…The presence of glycosidic forms of quercetin has also been reported in Carolina locust ( Dissoteira carolina ) as resulting from the absorption of quercetin glycosides from the plant tissues [ 27 ]. Overall, our data on the phenolic composition of insect-added cooked burgers are difficult to compare with the existing literature; in this regard, the majority of the published works are based only on the evaluation of the technological properties of the formulated meat products (such as texture parameters, color, and cooking properties) [ 28 , 29 ]. For example, Cavalheiro et al [ 29 ] recently tested the potential of cricket ( A. domesticus ) flour as a lean meat replacer in the development of beef patties, demonstrating that the incorporation of up to 5.0% ( w / w ) of cricket flour into beef patties was optimal in terms of the composition, technological, sensorial, and cooking properties.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, Choi et al (2017) reported that the addition of yellow worms ( T. molitor L.) to Frankfurt could reduce CIE L*-value but increase CIE a* and CIE b*-value. Lemke et al. (2023) reported that the addition of 20% insects to sausage products reduced in CIE L*-value compared to 10%.…”
Section: Resultsmentioning
confidence: 99%
“…During the measurements, D65 standard illuminant light source, 8 • angle of viewing, CIE 2 • Standard Observer, and a 30 mm measuring diameter were set. Additionally, based on the obtained L*, a*, and b* color parameter, the total color difference (∆E) was calculated using Equation (7):…”
Section: Colormentioning
confidence: 99%